3D titanium scaffold properties and osteogenesis of stem cells - Rohaya Megat Abdul Wahab; Manal Nabil Hagar; Nur Atmaliya Luchman; Farinawati Yazid; Shahrul Hisham Zainal Ariffin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Studies on porous titanium for use in dental applications have been growing due to their excellent properties such as low elastic modulus, biocompatibility and excellent strength. The porosity and pore size of titanium scaffold play an important role in bone formation. Thus, this paper reviews the properties of titanium scaffold and the relationship between the porosity and pore size of titanium with the osteogenesis of stem cells in respect of its mechanical properties and biological assessment. From this review, it was found that a pore size of less than 300 μm allows for good vascularization that can lead to direct osteogenesis without an interphase of cartilage formation. The minimum requirement for pore size is approximately 100 μm to assist in the migration requirement, cell size and transport, as a smaller pore size causes a hypoxic condition and induces osteochondral formation before osteogenesis, while a pore size from 500 to 1000 μm affects the differentiation of the stem cells. In addition, it was found that high porosity induces osteogenesis. The average porosity of the scaffold for cell proliferation was between 25-50 μm. In conclusion, highly porous titanium is a useful modern material for creating 3D structures for bone regeneration and implant fixation.